Hepatic lipidomics and proteomics analysis reveals the mechanism of Cyclocarya paliurus flavonoids in preventing non-alcoholic steatohepatitis in mice. (December 2022) - Wang, Yu-Yan; Lu, Shi-Juan; Gui, Rui; Wu, Jian-Ping; Li, Jing; He, Xiao-Ai; Zhang, Wei; Deng, Gui-Ming; Wang, Wen-Xuan; Long, Hong-Ping; Wei, Xi-Fan; Zeng, Guang-Yao; et al.
Graphical abstract: Highlights: Cyclocarya paliurus flavonoids supplementation can ameliorate hepatic steatosis via significantly lipid-lowering, antiinflammation and antifibrosis. Lipidomics indicated that the efficacy of preventing NASH was closely associated with the decreasing levels of triglycerides, diacylglycerols, and ceramides revealed by hepatic lipidomics analysis. Proteomics and PCR revealed that the related target of CPF promoted metabolic homeostasis in liver is acetyl-CoA carboxylase 1. Abstract: Cyclocarya paliurus flavonoids (CPF) are the main active ingredients, showed hypolipidemic, hypoglycemic, anti-lipogenic, and anti-inflammatory activities. However, the biomarkers associated with lipid metabolism and the underlying mechanisms for non-alcoholic steatohepatitis (NASH) of CPF have remained unclear. Herein, we combined lipidomics with proteomics to clarify its efficacy and related mechanisms of preventing NASH in mice. CPF supplementation (100 mg/kg) not only significantly decreased body and liver weight gain, cholesterol and triacylglycerols (TGs) levels in NASH mice without affecting feeding, but also ameliorated hepatic steatosis via significantly reducing liver inflammation score and the area of liver fibrosis. Lipidomics indicated that the efficacy of preventing NASH was closely associated with the decreasing levels of TGs, diacylglycerols (DGs), and ceramides (Cers). Moreover, proteomics also revealed that CPF promoted metabolic homeostasis in liver. The related target, acetyl-CoA carboxylase 1 and collagen type I alpha 1, were validated by proteomics and PCR. These above findings indicated that the remodulation of lipid homeostasis may be the pivotal pathway for the potential mechanisms of CPF in protecting against NASH.